2012
DOI: 10.1017/s1041610212000099
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of the prevalence of and risk factors for elderly depression between urban and rural populations in Japan

Abstract: Although factors related to depression did not differ markedly between urban and rural elderly people, some risk factors differed between the two areas. Effective intervention programs for elderly depression should pay more attention to regional differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
35
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 22 publications
5
35
4
1
Order By: Relevance
“…In line with other recent studies on OA, we found significant association between the presence of depressive symptoms and a number of variables at the individual level, in particular: female [17], [40][43], absence of an intimate partner [17], [41][43], a low educational level or illiteracy [17], [41][42], lack of empowerment in household decision-making (especially with regard to financial matters) [43][44], disability or functional limitations [40][41], presence of comorbidity [40][43], and chronic exposure to psychosocial stress [42]. The latter could be an important factor in the strong connection we found between depressive symptoms and self-reported incidents of physical violence or accidents in the previous 12 months.…”
Section: Discussionsupporting
confidence: 92%
“…In line with other recent studies on OA, we found significant association between the presence of depressive symptoms and a number of variables at the individual level, in particular: female [17], [40][43], absence of an intimate partner [17], [41][43], a low educational level or illiteracy [17], [41][42], lack of empowerment in household decision-making (especially with regard to financial matters) [43][44], disability or functional limitations [40][41], presence of comorbidity [40][43], and chronic exposure to psychosocial stress [42]. The latter could be an important factor in the strong connection we found between depressive symptoms and self-reported incidents of physical violence or accidents in the previous 12 months.…”
Section: Discussionsupporting
confidence: 92%
“…The pattern of rural-urban differences in depression observed among older adults in China is very different from that found in other countries (e.g., Britain, Canada, Japan, Korea, Taiwan and United States) where either no significant difference (Abe, Fujise, Fukunage, Nakagawa, & Ikeda, 2012; Kim, Shin, Yoon, & Stewart, 2002; St John, Blandford, & Strain, 2006) or a rural advantage (Chiu, Chen, Huang & Mau, 2005; Evans, 2009; Friedman, Conwell, & Delavan, 2007; Kim, Stewart, Shin, Yoon, & Lee, 2004; Walters et al, 2004) has been reported. Why is the prevalence of depression higher in rural than urban older adults in China?…”
contrasting
confidence: 91%
“…In the elderly population, it is well known that sociodemographic correlates of depression include female gender, divorced or separated marital status, low income and/or educational level, inadequate social support, and recent undesirable and unexpected life events26,27. In this study, lower education level was indeed a risk factor for depression, although we were not able to identify other sociodemographic variables that independently predicted depression.…”
Section: Discussioncontrasting
confidence: 56%
“…With the elderly population growing worldwide, geriatric depression is a major health concern that can be life threatening if not recognized in time and properly managed. This is a disease that significantly reduces quality of life and also is the single most important predictor of suicide27. In particular, physical health has a major impact on a person's mood and well-being, and geriatric skin disorders often represent a symptom or complication of an underlying systemic disease.…”
Section: Discussionmentioning
confidence: 99%